Correlation between HbA1c and Triglyceride Level with Coronary Stenosis Degree in Type 2 Diabetes Mellitus with Coronary Heart Disease - Adninta, Laily; Samsuria, Indranila; Limijadi, Edward Kurnia Setiawan (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: The mortality of coronary heart disease (CHD) in type 2 diabetes mellitus (DM) increased 2–4 times more than non-diabetics because of coronary stenosis. One of the risk factors for CHD in type 2 DM is dyslipidemia. Hypertriglyceridemia plays an important role in atherosclerosis coronary arteries theoretically. AIM: This study analyzed the parameters of HbA1c and triglyceride levels with the stenosis severity of coronary artery that occurs in type 2 DM patients with CHD that has not been analyzed so far. METHODS: This study was a cross-sectional observational analytic study. Forty patients of type 2 DM with CHD in Kariadi Hospital on September 2013 were recruited based on the inclusion and exclusion criteria. HbA1c level in plasma was measured by turbidimetric immunoassay method. Triglyceride level was measured by enzymatic methods. Coronary stenosis was based on coronary angiography result as percentage. Spearman correlation test was used and p < 0.05 was considered statistically significant. RESULTS: Mean HbA1c and triglyceride levels were 8.89 ± 1.498 % and 220.97 ± 92.24 mg/dL. The correlation test between HbA1c and triglycerides (TG) level with coronary stenosis, respectively, was p <0.001, r = 0.665; p = 0.001, r = 0.501. In addition, correlation between HbA1c and TG was p = 0.002, r = 0.466. CONCLUSION: HbA1c and triglyceride levels increase in line with the increasing stenosis severity of coronary heart disease in patients with type 2 DM.